EFISIENSI PEMASARAN EMPING JAGUNG PULUT DALAM RANGKA PENGEMBANGAN USAHA DI KELURAHAN OESAPA KECAMATAN KELAPA LIMA KOTA KUPANG - Bonifasius F. P. E. Tipas; Maria Bano; Sondang S. P. Pudjiastuti (Undana Press, 2023)
This study aims to determine the number of marketing channels for the corn chips agroindustry business, the marketing margin of the corn chips agro-industry business, and the marketing efficiency of the corn chips agro-industry business in Sakura SMEs, Kupang City. Data collection was obtained by means of direct interviews and questionnaires with respondents and observations made by researchers were activities in the corn chips marketing channel. The data analysis used in this research is descriptive analysis. The results of this study indicate that the marketing channel of corn chips uses two marketing channels, namely marketing channel I, producers selling products directly to consumers, and marketing channel II, producers selling products to retailers, then retailers selling products to consumers. The marketing margin for channel level I is Rp.0, - while in channel level II, the marketing margin generated by retailers is Rp.5,000. The marketing efficiency in channel I is 2.5 percent and in channel II the marketing efficiency is 2.30 percent.